(untitled) (The Agriculturists, 2017)
An experiment was conducted at the research field of Horticulture Research Centre, BARI, Gazipur during Rabi season of 2012-13 to 2014-15 to evaluate the yield and yield attributes of Marigold (var. BARI Marigold-1) to different doses of N, P and K fertilizers and to find out the optimum and economic doses of NPK for maximizing flower yield. Eleven treatments as T1, T2, T3, ,T10 and T11 comprising with four levels of fertilizer nutrients each of N (0, 60, 90 and 120 kg ha-1), P (0, 30, 40 and 50 kg ha-1) and K (0, 60, 90 and 120 kg ha-1) along with a blanket dose of 2 kg B and 4 kg Zn ha-1. The experiment was conducted assigning the treatments in a randomized complete block design with three replications. Flower yield and yield attributes of marigold significantly increased with NPK fertilizer for all three years. The significantly highest flower yield (22.25, 27.38 and 25.15 ton ha-1) was obtained from T3 treatment applying the nutrients N90P40K90 kg ha-1 along with blanket dose of 2 Kg B and 4 kg Zn ha-1 for the years 2012-13, 2013-14 and 2014-15, respectively which was statistically identical with T4 treatment (N120P40K90 kg ha-1) for the year 2012-13, but significantly different from all other treatments for the years 2013-14 and 2014-15, respectively. Flower yields were increased in T3 treatment (N90P40K90 kg ha-1) by 81.34, 62.53 and 49.53%; 146.00, 119.39 and 108.84% and 121.20, 92.13 and 84.11% over their control in respect to the years 2012-13, 2013-14 and 2014-15. The highest benefit-cost ratio 7.14 was obtained from T3 (N90P40K90 kg ha-1) followed by T4 (6.53) treatment. From the quadratic regression equation averaging three years data the optimum and economic doses 103.75 and 102.44 kg N; 36.67 and 36.31 kg P and 90.10 and 88.43 kg K, respectively were found which could be recommended for marigold production in Grey Terrace Soil of Joydebpur under AEZ 28. The Agriculturists 2017; 15(1) 101-109